EVALUATION OF SMART MICROGRID TO IMPROVE ELECTRICITY SUPPLY AVAILABILITY AND RENEWABLE FRACTION AT THE UNIVERSITY BUILDING - Salsabila
The Energy Management Laboratory received grant funding from the Ministry of Energy and Mineral Resources and the West Java Provincial Government for the development of smart microgrids in the CAS ITB Building. However, due to a major blackout on August 4 2019, the focus of the project has changed to a smart microgrid for energy security on TEM critical facility. The installation process has been carried out since November 2019 and all major components have been connected, but due to the COVID-19 pandemic the data acquisition system has not been installed so that the performance of the smart microgrid cannot be directly monitored and evaluated. This research aims to evaluate the performance of smart microgrids to increase the availability of electricity supply by conducting energy analysis (simulation of energy production and consumption) and economic analysis in testing the reliability and resiliency of electricity supply. The simulations are divided into three scenarios, such as the basic scenario, the test scenario, and the recommendation scenario. The test scenario consists of system capacity test, component replacement, and sensitivity analysis. The results of the basic scenario simulation show that the availability of electricity supply for the 2019 blackout profile is fulfilled, with a renewable fraction (RF) of 30,5%; the cost of energy (CoE) Rp2.019/kWh; and battery autonomy (BA) of 11,1 hours. From the analysis of test scenario result, several recommendations will be implemented, namely replacing battery components and photovoltaic modules, adding battery capacity, and setting the SoC limits on the battery to increase the renewable fraction. The results of the recommendation scenario simulation show that it is succeeded in increasing the availability of electricity supply and reaching the target with a BA value of 37 hours and an RF value of 46,4% at the start of the project cycle period; and BA of 25,5 hours and RF of 29,1% at the end of the project cycle period, with an economic value of Rp6,448/kWh.